Diversity and singularity of training conditions in special education teaching during internships: a comparison with actual working conditions - Delorme, Coralie (Swiss Journal of Educational Research, 2023)
Little is known about the conditions that future special education teachers encounter during their initial teacher training internships. The aim of this article is to describe, using filmed, transcribed and analyzed observation data, the training conditions experienced by five trainees during initial training periods in Geneva in different special education teaching contexts. The results show that the training conditions are very similar to the actual working conditions of special education teachers. They highlight their singularity and diversity, as well as their formative aspect, but also reveal the risks of such proximity for the trainees’ training.